Improving cytocompatibility of CdTe quantum dots by Schiff-base-coordinated lanthanides surface doping - Hana Buchtelova; Vladislav Strmiska; Zuzana Skubalova; Simona Dostalova; Petr Michalek; Sona Krizkova; David Hynek; Lukas Kalina; Lukas Richtera; Amitava Moulick; Vojtech Adam; Zbynek Heger (Journal of Nanobiotechnology, 2018)
Abstract Background Suitable fluorophores are the core of fluorescence imaging. Among the most exciting, yet controversial, labels are quantum dots (QDs) with their unique optical and chemical properties, but also considerable toxicity. This hinders QDs applicability in living systems. Surface chemistry has a profound impact on biological behavior of QDs. This study describes a two-step synthesis of QDs formed by CdTe core doped with Schiff base ligand for lanthanides [Ln (Yb3+, Tb3+ and Gd3+)] as novel cytocompatible fluorophores. Results Microwave-assisted synthesis resulted in water-soluble nanocrystals with high colloidal and fluorescence stability with quantum yields of 40.9–58.0%. Despite induction of endocytosis and cytoplasm accumulation of Yb- and TbQDs, surface doping resulted in significant enhancement in cytocompatibility when compared to the un-doped CdTe QDs. Furthermore, only negligible antimigratory properties without triggering formation of reactive oxygen species were found, particularly for TbQDs. Ln-doped QDs did not cause observable hemolysis, adsorbed only a low degree of plasma proteins onto their surface and did not possess significant genotoxicity. To validate the applicability of Ln-doped QDs for in vitro visualization of receptor status of living cells, we performed a site-directed conjugation of antibodies towards immuno-labeling of clinically relevant target—human norepinephrine transporter (hNET), over-expressed in neuroendocrine tumors like neuroblastoma. Immuno-performance of modified TbQDs was successfully tested in distinct types of cells varying in hNET expression and also in neuroblastoma cells with hNET expression up-regulated by vorinostat. Conclusion For the first time we show that Ln-doping of CdTe QDs can significantly alleviate their cytotoxic effects. The obtained results imply great potential of Ln-doped QDs as cytocompatible and stable fluorophores for various bio-labeling applications.